Surprised by supermarkets: Diffusion of modern food retail in India - Reardon, Thomas; Minten, Bart (Emerald Publishing Limited, 2011)
The purpose of this paper is to analyze the patterns and dynamics of the diffusion of modern food retail in India.The paper is based on detailed sales data from retail chains in India, short case studies of retail chains, and review of literature.The article presents three surprises concerning modern food retail diffusion in India. First, modern retail has developed in three “waves”, with the first wave, government retail chains, starting in the 1960s/1970s, cooperative retail chains starting in the 1970s/1980s, and private retail chains in the 1990s/2000s. All three were substantial, and internationally uniquely, all three coexist in the 2000s as segments of modern retail. Second, the rise of modern private retail in India in the past six years has been among the fastest in the world, growing at 49 percent a year on average over that period, and bouncing back to growth after a dip from the recent recession. The great majority of modern private retail has arisen in 2007‐2010. Third, beside the uniqueness of the coexistence of three types of retail noted above, Indian private retail chain development has unique or rare characteristics: driven by domestic capital investment, “early” (in terms of usual international patterns) diversification into small formats, “early” penetration of small cities and even rural towns, of the food markets of the poor and lower‐middle class, and of fresh produce retail. These unique factors have helped to propel it quickly.For the first time in the literature, the paper presents an analysis of: the three waves in Indian retail; detailed sales data for all leading chains; and its uniqueness.